Refraction in the Tele-Optometric Examination Compared to Traditional In-Person Refraction in an Adult Population. - Morettin, Christina E.; Randhawa, Harneet K.; McLeod, Heather M.; Fazio, Kimberly; Kattouf, Valerie M.; Patel, Jaymeni (Optometry & Visual Performance, 2023)
Background: Globally, access to reliable, affordable tools that provide refractions and ultimately accurate spectacle prescriptions will aid in improving eye health. Our study aimed to evaluate a tele-optometric remote refraction compared to a traditional in-person subjective refraction. Methods: A cohort of 30 pre-presbyopic participants ≥18 years of age at the Illinois College of Optometry were recruited to participate in this pilot study. Participants completed two comprehensive eye examinations. First, the teleoptometric comprehensive eye examination was completed using the DigitalOptometrics platform. A remote technician completed refraction, followed by videoconferencing with an investigator optometrist. This remote eye examination was then followed by the in-person comprehensive eye examination by a different investigator optometrist, with a traditional manifest refraction. Both modalities used a Reichart VRx digital phoropter. Results: A total of 60 eyes were evaluated using both testing methods. The mean spherical equivalent, spherical power, cylindrical power, and axis in the tele-optometric remote refractions were -3.69 D ± 2.81 D, -3.35 D ± 2.68 D, -0.70 D ± 0.81 D, and 78 ± 77 degrees, respectively, compared to -3.58 D ± 2.80 D, -3.23 D ± 2.69 D, -0.68 D ± 0.71 D, and 81 ± 76 degrees in the in-person refraction group, respectively. No statistically significant difference was found between the spherical equivalent, spherical, cylindrical, and axis components of the prescriptions found in the tele-optometric examination compared to the in-person examination (p=0.82, p=0.82, p=0.93, p=0.85, respectively). Ten percent (6) of the eyes (4 hyperopic and 2 myopic) were over-minused in the tele-optometric examination. Conclusions: Using the DigitalOptometrics platform, tele-optometric remote refraction by a technician was not significantly different when compared to a traditional in-person manifest refraction in a young, healthy, pre-presbyopic adult-student cohort. Attention must be paid to low hyperopes and high myopes to ensure that they are not over-minused in remote refractions.